DEVELOPING ANIMATED VIDEO FOR WATER CYCLE TOPIC IN FIFTH GRADE OF ELEMENTARY SCHOOL - Hani, Ma'iswati; Yulistia, Arin; Anindya, Arini; Islamiati, Asti; Alwini, Selin Nadia; Nuryadin, Asep (PIONIR: JURNAL PENDIDIKAN, 2024)
The low level of student motivation in studying the water cycle has resulted in reduced instructional effectiveness. This factor is attributed to the limited utilization of technology by teachers to enhance the appeal of the learning process, with teachers predominantly relying on textbooks as the primary instructional resource. The research aims to evaluate the validity and practicality of animated video media as a supplementary tool for understanding the subject matter and fostering learning motivation, specifically concerning the water cycle topic for 5th- grade elementary school students. Data were obtained through the ADDIE model phases (Analysis, Design, Development, Implementation, Evaluation). The research findings indicated that the material presented in the instructional videos exhibits a remarkably high level of suitability for delivery to students, with an average validation percentage of 100% by subject matter expert and 95,14% by media expert. Additionally, an evaluation of the practicality of this media revealed an average percentage of 89% from student feedback and 100% from teacher assessment. Consequently, it can be inferred that this animated video product is both valid and practical for utilization within the realm of educational instruction.Keywords: learning media, animated video, water cycle.